Comparative scanning electron microscope study of the degradation of a plasticized polyvinyl chloride waterproofing membrane in different conditions - A. Pedrosa; M. Del Río (Materiales de Construccion, 2017)
This paper discusses the analysis of several samples of a plasticized polyvinyl chloride (PVC-P) waterproofing membrane. The samples were extracted from different areas of the same flat roof, which was in service for over 12 years. An original sample of an identical PVC-P membrane that was not installed on the roof was also analyzed. The analysis of the materials was carried out using a scanning electron microscope (SEM). An elemental analysis of every sample was also performed by energy dispersive X-ray spectroscopy (EDS). Micrographs and the elemental composition of the samples were compared with the data obtained in the analysis of the original sample. The results show dehydrochlorination of the polymer in two of the samples studied and great deterioration that was not visible to the naked eye in the sample that was totally exposed to the weather.